Scaffolding the development of problem-solving skills in chemistry: guiding novice students out of dead ends and false starts. Issue 3 (15th May 2017) - Yuriev, Elizabeth; Naidu, Som; Schembri, Luke S.; Short, Jennifer L.
Abstract : To scaffold the development of problem-solving skills in chemistry, chemistry educators are exploring a variety of instructional techniques. In this study, we have designed, implemented, and evaluated a problem-solving workflow – "Goldilocks Help". This workflow builds on work done in the field of problem solving in chemistry and provides specific scaffolding for students who experience procedural difficulties during problem solving, such as dead ends (not being able to troubleshoot) and false starts (not knowing how to initiate the problem-solving process). The Goldilocks Help workflow has been designed to scaffold a systematic problem-solving process with a designation of explicit phases of problem solving, to introduce students to the types of questions/prompts that should guide them through the process, to encourage explicit reasoning necessary for successful conceptual problem solving, and to promote the development of metacognitive self-regulation skills. The tool has been implemented and evaluated over a two-year period and modified based on student and instructor feedback. The evaluation demonstrated a shift in students' beliefs in their capacities to use the strategies required to achieve successful problem solving and showed their capacity to employ such strategies.